2020
DOI: 10.3389/fsufs.2020.00022
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Beauveria bassiana Into an Integrated Pest Management Plan for Coffee Berry Borer in Hawaii

Abstract: Since its recent establishment in Hawaii, the coffee berry borer (CBB), Hypothenemus hampei (Coleoptera: Curculionidae), threatens yields, quality, and price of coffee production. A limited number of insecticides (primarily Beauveria bassiana) are used to control CBB with minimal disruption in this agroecosystem. We evaluated two insecticide spray strategies across eight coffee farms in the Kona and Ka'u districts of Hawaii Island. Coffee growers sprayed insecticides approximately monthly (calendar basis) or e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…Coffee berries on the ground may be previously infested while on the plants, but heavy rains may accelerate their decay, preventing CBB infestation ( Cárdenas and Baker 2010 ). The sustainable management program for CBB has to consider the concept of integrating other methods, such as the use of Beauveria bassiana which has successfully been used in Colombia ( Bustillo et al 1998 ) and Hawaii ( Greco et al 2018 , Hollingsworth et al 2020 ), the use of baited traps with semiochemicals to monitor flight activity and control and, if possible, using natural enemies (such as parasitoids, predatory ants, and flat bark beetles) that may be present in the area, with adoption of cultural control practices such as sanitation.…”
Section: Discussionmentioning
confidence: 99%
“…Coffee berries on the ground may be previously infested while on the plants, but heavy rains may accelerate their decay, preventing CBB infestation ( Cárdenas and Baker 2010 ). The sustainable management program for CBB has to consider the concept of integrating other methods, such as the use of Beauveria bassiana which has successfully been used in Colombia ( Bustillo et al 1998 ) and Hawaii ( Greco et al 2018 , Hollingsworth et al 2020 ), the use of baited traps with semiochemicals to monitor flight activity and control and, if possible, using natural enemies (such as parasitoids, predatory ants, and flat bark beetles) that may be present in the area, with adoption of cultural control practices such as sanitation.…”
Section: Discussionmentioning
confidence: 99%
“…After crude oil, coffee is the most traded commodity in the world [36]. Coffee is grown on more than 10 million hectares of land worldwide, mainly in tropical and subtropical regions, justifying the largest coffee producers in the world being Brazil (36%), Vietnam (17%) and Colombia (8%) [27], [44] and represents a significant part of the Gross Domestic Product of these countries. Produced in more than 70 countries, the largest amount of coffee is produced in developing countries, and the largest consumption of beverage is in developed countries, whose growing demand has doubled the amount of coffee grown in the last decade [45], [46].…”
Section: A Coffee Productionmentioning
confidence: 99%
“…A recent study examining calendar (≈monthly) vs. threshold (based on field monitoring data) spray strategies of B. bassiana found that farms adopting the threshold strategy applied B. bassiana early in the season (May–July) and required fewer sprays to achieve the same level of control achieved with calendar sprays, resulting in a net benefit [ 203 ]. Research on the effect of dosage suggests that reduced rates (16 oz per acre) of BotaniGard ® ES may be just as effective as the recommended rate (32 oz per acre) in controlling CBB, particularly when combined with acceptable sanitation practices (L. Keith and S. Wraight, pers.…”
Section: Current State Of Cbb Management: Hawaii As a Case Studymentioning
confidence: 99%